2018
DOI: 10.1016/j.ehj.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking imaging as a predictor of left ventricular remodeling 6 months after first anterior ST elevation myocardial infarction in patients managed by primary percutaneous coronary intervention

Abstract: Acute myocardial infarction (AMI) remains a leading cause of morbidity and mortality worldwide. LV remodeling is an important factor in the pathophysiology of advancing heart failure (HF).Aim of the workTo evaluate the value of speckle tracking imaging as a predictor of left ventricular remodeling 6 months after first anterior STEMI in patients managed by primary PCI.MethodologyEighty-five patients with first acute anterior STEMI underwent primary PCI. Patients were followed up for 6 months. Echocardiographywa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…По данным I. Bastawy с соавт. [17] средний пиковый систолический ГПД>-12.5% является независимым предиктором ремоделирования ЛЖ.…”
Section: Discussionunclassified
“…По данным I. Bastawy с соавт. [17] средний пиковый систолический ГПД>-12.5% является независимым предиктором ремоделирования ЛЖ.…”
Section: Discussionunclassified
“…In studies comparable to ours, a GLS value of −12% to −14% was independently associated with mortality, heart failure, and stroke. 19,25,26 These results may provide valuable information for the clinical treatment of patients with hypertension and AMI.…”
mentioning
confidence: 89%
“…Myocardial deformation is linked to the longitudinally oriented fibers, located in the sub-endocardium, which are the most susceptible to ischemic changes. It was demonstrated in many studies that GLS detects longitudinal abnormalities in the absence of reduction in LVEF [22][23][24][25]. This is due to the fact that fibers located in the mid-wall, which are circumferentially oriented, may compensate in the case of reduction of the longitudinal mechanics in order to maintain LVEF normal.…”
Section: Gls Versus Lvef In the Prediction Of Remodeling And Hf Of Ami Patientsmentioning
confidence: 99%
“…Lacalzada et al demonstrated that GLS (>-12.46%) was a predictor of adverse remodeling and cardiac events in patients with AMI [31]. Moreover, Bastawy et al demonstrated that GLS (>-12.5%) and LV torsion (< 9.5°) early after anterior STEMI treated with primary PCI are independent predictors of six months LV remodeling [24].…”
Section: Gls Versus Lvef In the Prediction Of Remodeling And Hf Of Ami Patientsmentioning
confidence: 99%